2021
DOI: 10.1038/s41598-021-84408-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inflammatory interleukins and selected miRNAs in non-small cell lung cancer

Abstract: Tumours are characterised by an ability to avoid immune destruction and the presence of cancer-associated inflammation. Better understanding of the link between lung cancer and such inflammation is vital for early detection and personalized treatment. Thus, we examined the mRNA expression of interleukins IL-1β, IL-6, IL-17 and miR-9, miR-122 as potential useful biomarkers of NSCLC. Tumour tissues, non-cancerous tissue and blood samples were collected from 39 patients with primary NSCLC undergoing surgical trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…32 Exosome production varies according to different cell states. Dutkowska et al 33 evaluated the expression of interleukin (IL)-1β, IL-6, and IL-17 in tumours versus surgical margins, and observed significantly higher expression of IL-6 in tumours relative to adjacent tissue, thereby indicating that inflammatory processes play a role in tumorigenesis. Additionally, they evaluated miR-9 and miR-122 as cytokine regulators in pre-and postoperative peripheral blood exosomes, revealing elevated levels of both miRs after tumour resection.…”
Section: Exosomes Exosome Formation and Productionmentioning
confidence: 99%
“…32 Exosome production varies according to different cell states. Dutkowska et al 33 evaluated the expression of interleukin (IL)-1β, IL-6, and IL-17 in tumours versus surgical margins, and observed significantly higher expression of IL-6 in tumours relative to adjacent tissue, thereby indicating that inflammatory processes play a role in tumorigenesis. Additionally, they evaluated miR-9 and miR-122 as cytokine regulators in pre-and postoperative peripheral blood exosomes, revealing elevated levels of both miRs after tumour resection.…”
Section: Exosomes Exosome Formation and Productionmentioning
confidence: 99%
“…It was observed that the expression of selected interleukins in noncancerous tissues was significantly higher than that in tumor tissues, and patients with a history of 40 pack-years (PY) (2,197, IQR: 0.821-4.415) and who were over 40 years old (0.461, IQR: 0.372-0.741; p = 0.037) had significantly greater levels of IL-6 in their tumor tissues. The up-regulation of IL-1 and IL-6 in tumors and surrounding tissues suggests that firing cycles have a role in NSCLC, and smoking can affect inflammation during tumorigenesis, which is manifested by an increase in IL-6 in patients' tumor tests [18].…”
Section: Fagerstrom Nicotine Dependence Test and Lipopolysaccharide Level Correlationmentioning
confidence: 99%
“…Additionally, CRP disrupted the relationship between smoking and hypertension, accounting for 58.59 percent of smoking's estimated causal effect on hypertension [18], [19]. Furthermore, some previous studies focus on the heavy smokers in Bayi.…”
Section: Fagerstrom Nicotine Dependence Test and Lipopolysaccharide Level Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin 6 (IL-6), a multifunctional proinflammatory cytokine, is produced by different cells, including immune cells, endothelial cells, cancer-associated fibroblasts, and tumor cells (Islas-Vazquez et al, 2020;Dutkowska et al, 2021). IL-6 is involved in the regulation of tumorigenesis, progression, and metastasis and its overexpression is particularly strongly associated with a poor prognosis for NSCLC (Kiss et al, 2020;Pan et al, 2020;Su et al, 2020).…”
Section: Introductionmentioning
confidence: 99%